Limitação por sódio em assembléias de formigas no cerrado - Vieira, Jésica (2014)
A major challenge for any animal is to maintain the balance of multiple nutrients in the body, in the face of a nutritionally heterogeneous environment. Sodium (Na) is an essential nutrient for life and although it is well know that they are a limiting nutrient for many organisms, including ants, little is known to what extent this nutrient may be beneficial. In this work we investigated the use of ant communities for baits containing salt or sucrose in different Cerrado physiognomies along a gradient of increasing vegetation cover and litter and decreasing grass cover. A field experiment was also conducted to determine the effect of sodium supplementation on the development of colonies of a common cerrado arboreal ant species (Cephalotes pusillus). We distributed baits with different concentrations of salt and sucrose in areas of open cerrado, cerrado stricto sensu, dense cerrado and cerradão. For the experiment, 40 incipient colonies of C. pusillus were transplanted to artificial wood nests, each containing a queen, two soldiers and twenty workers. The artificial nests were placed in a common Cerrado tree species (Qualea grandiflora). During the experiment the colonies received four different treatments. Ten nests were fed with a solution with salt at 1%, ten with a solution of 14% sucrose and 1% of one amino acid, ten trees with sucrose, amino acid and salt and ten control trees with distilled water. On the vegetation, the ants preferred the baits containing salt, while on the soil they preferred the sucrose baits. This pattern was the same in all vegetation types. The use of the ants for baits containing salt or sucrose was different in phylogenetically distant genera, what can be better explained by the variation on its food habits. Genera which the main food source is in form of liquid sugary exudates, like Azteca, Cephalotes and Camponotus preferred the salt baits. The sucrose baits, on the other hand, were preferred by predatory genera, like Ectatomma, Pachycondyla, Pheidole e Nylanderia. Of the experimental colonies of C. pusillus, the ones that were fed with a salt solution produced fewer eggs, larvae and pupae than the colonies of the other treatments. This shows that although sodium is an apparently limiting element for some genera, when consumed in excess, it can inhibit the development of the colony.